PENGGUNAAN KOMBINASI KUNYIT (Curcuma domestica) DAN JAHE (Zingiber officinale) BENTUK ENKAPSULASI DAN TANPA ENKAPSULASI TERHADAP KARAKTERISTIK USUS DAN MIKROFLORA USUS AYAM PEDAGING - Muhammad Halim Natsir (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
The purpose of this research was to examine the use of curcuma (curcuma domestica) and ginger (Zingiber officinale) combinations with encapsulated and not Encapsulated on intestinal histological and Intestinal Microflora in broiler. The materials used in this research were 180 day-old broiler chicks, flour and encapsulated turmeric and ginger mixture. The encapsulants used were maltodextrin (75 %: casein 25 %) and adding BHT 0.075 % from extract of 10 % turmeric and ginger mixture. The methods used a Laboratory experiment of a Completely Randomized Design with 9 treatments (P0 = control feed), namely 2 forms of turmeric and ginger mixture. (flour and encapsulated) with 4 levels (0.2; 0.4; 0.6 and 0.8%). The results showed that use of turmeric and ginger mixture in the form of non-encapsulation and encapsulation significantly improved (P<0.01) pH, viscocity of digesta and the number of villi, but showed a no significant difference on villi height, and the number of bacteria (LAB, Lactobacillus, sp, E Coli and salmonella Sp.). It is concluded that the use of turmeric and ginger mixture of encapsulated form provides better results than the form of non- encapsulation with the optimum level of 0.8%. Therefore using encapsulated form in 0.8% of the combined turmeric and ginger in broiler diet is recommended. (Key words: Broiler, Encapsulation, Ginger, Histological, Microflora, Turmeric)